2015
DOI: 10.1016/j.pmedr.2015.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Parental education and text messaging reminders as effective community based tools to increase HPV vaccination rates among Mexican American children

Abstract: ObjectiveLatino populations, particularly Mexican-Americans who comprise 65% of the Latinos in the U.S., are disproportionately affected by HPV-related diseases. The HPV vaccination completion rates remain low, well below the Healthy People 2020 goal. In this study we assessed the effect of parental education and a text messaging reminder service on HPV vaccine completion rates among eligible children of Mexican American parents.Study designNonequivalent group study of Mexican parents of HPV vaccine eligible c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 13 publications
2
32
0
2
Order By: Relevance
“…The establishment of a high-risk reminder reporting system has shortened the delivery time of critical healthcare to patients with high-risk symptoms. 27 Text messages can be quickly sent from radiologists to clinicians upon detection of high-risk symptoms, and immediate risk management actions can be taken in response. 28 However, excessive and non-essential reporting of risk can likely compromise the efficacy of risk management in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of a high-risk reminder reporting system has shortened the delivery time of critical healthcare to patients with high-risk symptoms. 27 Text messages can be quickly sent from radiologists to clinicians upon detection of high-risk symptoms, and immediate risk management actions can be taken in response. 28 However, excessive and non-essential reporting of risk can likely compromise the efficacy of risk management in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56] Text messaging can also be combined with other intervention elements, such as in-person consultation, to increase the efficacy of the intervention. 57 In addition to simple reminders, text messages can also contain particular message features, such as educational messages about HPV and cancer, the source of the health threat, or the role of personal agency, to increase parental intention to vaccinate their children. 58,59 Text messaging may be a particularly promising area for increasing uptake of dose 1 and timely completion of the second HPV dose, especially given that the Pew Research Center reports that 73% of American adults are text messaging users, sending and receiving an average of 42 texts per dayand that report was done 6 years ago.…”
Section: Provider Trainingmentioning
confidence: 99%
“…Two studies directed at parents have also shown positive effects. Aragones (43) used a using a nonequivalent group design to test an education session plus text-messaging intervention compared to an education session intervention among Mexican-American parents with a child who needed the HPV vaccine. Based on parental report, there was an 88% series completion rate among those receiving the first HPV vaccine dose in the education plus text messaging group compared to 40% in the education only group (p=0.004).…”
Section: Discussionmentioning
confidence: 99%